Reasons for Differences in Perspective on Employee Behavior: Internal vs. External, Permanent vs. Temporary, Controllable vs. Uncontrollable - Göksoy, Süleyman (Language, Literature and Education: Research Updates Vol. 1, 2025)
People make attributions because of their need to have a consistent, balanced worldview, to understand, explain, predict and control the environment. People meet two basic needs by making attributions. The first is to have a consistent, balanced worldview, and the second is to gain control over their environment. In addition to the internal-external and permanent-temporary nature of the causes of behavior and events, it is also important whether the causes are controllable or uncontrollable. Attribution theory explains how people explain the behavior of others (e.g. character traits, motives and attitudes, that person's personality traits, abilities, efforts, mood, etc.) internally or by external circumstances such as luck, the person's circumstances, etc., in other words, by any situation or behavior that occurs outside the person. Naturally, attribution theory tries to explain how we judge people differently based on the meaning we attribute to a certain behavior. What is important in terms of social psychology is not which explanation is more accurate about the behavior, but why the person chooses an internal or external explanation. The fact that the reasons for behaviors and events are internal-external, permanent-temporary, and uncontrollable shows how difficult and complex it is to judge, perceive, and evaluate that behavior. As a result, it is not possible to expect everyone who is faced with a situation, event, or behavior to react the same way. Therefore, it would not be realistic to think that all employees in the organization will work with people who have exactly the same perspective.